Analytical Performance of a Multiplex Real-Time PCR Assay Using TaqMan Probes for Quantification of Trypanosoma cruzi Satellite DNA in Blood Samples - Duffy, Tomas (2013)
Background: The analytical validation of sensitive, accurate and standardized Real-Time PCR methods for Trypanosoma cruzi quantification is crucial to provide a reliable laboratory tool for diagnosis of recent infections as well as for monitoring treatment efficacy. Methods/Principal Findings: We have standardized and validated a multiplex Real-Time quantitative PCR assay (qPCR) based on TaqMan technology, aiming to quantify T. cruzi satellite DNA as well as an internal amplification control (IAC) in a single-tube reaction. IAC amplification allows rule out false negative PCR results due to inhibitory substances or loss of DNA during sample processing. The assay has a limit of detection (LOD) of 0.70 parasite equivalents/mL and a limit of quantification (LOQ) of 1.53 parasite equivalents/mL starting from non-boiled Guanidine EDTA blood spiked with T. cruzi CLBrener stock. The method was evaluated with blood samples collected from Chagas disease patients experiencing different clinical stages and epidemiological scenarios: 1- Sixteen Venezuelan patients from an outbreak of oral transmission, 2- Sixty three Bolivian patients suffering chronic Chagas disease, 3- Thirty four Argentinean cases with chronic Chagas disease, 4- Twenty seven newborns to seropositive mothers, 5- A seronegative receptor who got infected after transplantation with a cadaveric kidney explanted from an infected subject. Conclusions/Significance: The performing parameters of this assay encourage its application to early assessment of T. cruzi infection in cases in which serological methods are not informative, such as recent infections by oral contamination or congenital transmission or after transplantation with organs from seropositive donors, as well as for monitoring Chagas disease patients under etiological treatment.